2009
DOI: 10.1590/s0101-31222009000200001
|View full text |Cite
|
Sign up to set email alerts
|

Validação do aplicativo computacional SEEDSOLVE para previsão das perdas de germinação e vigor de sementes armazenadas

Abstract: RESUMO -Objetivou-se validar o aplicativo computacional SEEDSOLVE para previsão das perdas de germinação e vigor de sementes ortodoxas armazenadas. A validação foi realizada comparandose valores calculados com valores experimentais das perdas de germinação e vigor de sementes de três cultivares de milho e de soja armazenadas em laboratório, durante um período de 210 dias. Sementes de milho e soja, com três níveis de grau de umidade (11, 13 e 15% para o milho e 9, 11 e 13% para a soja), foram acondicionadas em … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
0
6
0
2
Order By: Relevance
“…Similar results have also been found by Contreiras Rodrigues et al (2011), but with osmoconditioned parsley seeds, who found that the maximum storage time was 90 days, being that degradation began already at the first month of storage. According Sinicio et al (2009), in the post-harvest stage, storage is one of the steps that most interferes with the quality of the seeds, as there are numerous factors involved.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results have also been found by Contreiras Rodrigues et al (2011), but with osmoconditioned parsley seeds, who found that the maximum storage time was 90 days, being that degradation began already at the first month of storage. According Sinicio et al (2009), in the post-harvest stage, storage is one of the steps that most interferes with the quality of the seeds, as there are numerous factors involved.…”
Section: Resultsmentioning
confidence: 99%
“…The prediction of viability loss of stored seeds is important both for the maintenance of germplasm and for the management of seed storage (Sinício et al 2009). Since the half past century studies have been developed in order to predict the viability loss, with survival curves and relationships between temperature, humidity and some measure of viability (Pritchard & Dickie 2003).…”
Section: Introductionmentioning
confidence: 99%
“…O processo de produção de sementes exige tecnologias desde a escolha da cultivar até a comercialização, que abrangem seleção da área, uso de variedades recomendadas, semeadura em épocas estabelecidas, acompanhamento do desenvolvimento vegetativo, práticas culturais, tratamentos fitossanitários, determinação do momento ideal de colheita e limpeza adequada dos equipamentos de transporte e beneficiamento (Marcondes et al, 2005;Sinício et al, 2009).…”
Section: Introductionunclassified